Explicit Vocabulary Instruction in an English Content-Area Coursewith University Student Teachers:When Comprehensible Input Needs to be Comprehended - Serna Dimas, Héctor Manuel (GIST – Education and Learning Research Journal, 2011)
This action research study explores explicit vocabulary instruction in an L2 (English) content-area course with a group of university student teachers. The study reviews several positions on the treatment of vocabulary in L2 contexts. The researcher takes up the teaching of explicit vocabulary through class activities and the students’ completion of vocabulary entries in a Word Study notebook. The data collection procedures included the teacher´s lesson plans, the students´ Word Study entries, and their opinions on both their vocabulary learning and their notebook completion through a final interview. Research findings reveal that the Word Study notebook did contribute to students’ learning since they had a grasp of the vocabulary used in the class in terms of participating in the instructional conversations led by the professor and doing the class activities.